Robert Koch (1843-1910): A Pioneer and Leader in Medicine and Bacteriology - Stadtländer, Christian (Medicina Historica, 2022)
Abstract. Robert Koch (1843‒1910) was a German physician and bacteriologist who was awarded the ‘Nobel Prize in Physiology or Medicine’ in 1905 for his tuberculosis research and the discovery of the causative agent of tuberculosis (Mycobacterium tuberculosis). He significantly improved many laboratory techniques and defined the ‘Koch’s postulates’ – strict criteria established for the proof of etiology of an infectious agent to cause disease in a host. He is also known as the discoverer of the causative microorganism of anthrax (Bacillus anthracis) and was the first researcher able to isolate and cultivate in pure culture the ‘comma bacillus’ (Vibrio cholerae) from patients with cholera. Furthermore, Koch worked on the etiology of wound infections and developed methods of water filtration, disinfection, and sterilization. This article about Robert Koch tells not only the story about his life and legacy as a pioneer and founder of modern bacteriology, but also provides an in-depth analysis of his leadership style which he further developed throughout his career, and which helped him rise to the level of an international leader with world fame in both science and medicine.